2001
DOI: 10.1111/j.1469-7793.2001.0219j.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on elementary steps of the cross‐bridge cycle in rabbit soleus slow‐twitch muscle fibres

Abstract: Isometric tension, stiffness and the cross‐bridge kinetics in rabbit soleus slow‐twitch fibres (STFs) were studied in the temperature range 5‐37°C by sinusoidal analysis. The effects of MgATP and phosphate (Pi) on the cross‐bridge kinetics were studied, and the temperature dependence of the kinetic constants of elementary steps of the cross‐bridge cycle was deduced in the range 20‐37°C. The MgATP association constant (K1a) decreased when temperature was increased. The rate constants of the ATP‐isomerization st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
76
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 54 publications
(107 reference statements)
14
76
2
Order By: Relevance
“…The MgATP-dependent cross-bridge detachment rates from skinned rat soleus fibers at 17 C (Fig. 4 K) are consistent with the 2pc-MgATP relationships measured in skinned rabbit soleus fibers at 20 C (37,38). Specifically, we show that the myosin detachment rate increased from 8. soleus fibers at 20 C (37) compared to rat soleus fibers at 17 C (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The MgATP-dependent cross-bridge detachment rates from skinned rat soleus fibers at 17 C (Fig. 4 K) are consistent with the 2pc-MgATP relationships measured in skinned rabbit soleus fibers at 20 C (37,38). Specifically, we show that the myosin detachment rate increased from 8. soleus fibers at 20 C (37) compared to rat soleus fibers at 17 C (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Assuming a duty cycle of ∼0.5 (Kaya and Higuchi, 2010), this translates to a duration of about 335 ms for the bound life of a cross-bridge in frog muscle contracting isometrically at 0°C. Studies of rabbit muscle fibers suggest that Q 10 values for cross-bridge detachment rates are quite high, between 3 and 4 (Wang and Kawai, 2001). For a Q 10 of 3, we would expect the process of detachment and reattachment to increase by a factor of 27 from 0 to 30°C; thus, the duration of binding for a cross-bridge would be less than 10 ms at typical avian or mammalian body temperatures.…”
Section: Cross-bridge and Myofilament Elasticitymentioning
confidence: 99%
“…ΔH° > 0 and ΔS° > 0 have been observed on actomyosin interaction in solution (Tonomura et al 1962;Highsmith 1977) and in myofibrils (Ishiwata et al 1986). ΔH° > 0, ΔS° > 0 and ΔC P < 0 have been observed in rabbit psoas fibres (Zhao and Kawai 1994a;Murphy et al 1996) and soleus slow twitch fibres (Wang and Kawai 2001) on the step that generates force. This mechanism is consistent with the well known observation that isometric tension increases with an increase in the temperature both in mammalian skeletal (Goldman et al 1987;Ranatunga et al 1987;Zhao and Kawai 1994a;Coupland et al 2001;Wang and Kawai 2001) and cardiac (Ranatunga 1999;) muscle fibres, and reviewed by Kawai (2003).…”
Section: Temperature Effect and Hydrophobic Interactionmentioning
confidence: 95%
“…That is, K 1 may change as a result of change in isometric tension. It was reported that the ATP binding step (K 1 ) may be influenced by loop 1 of myosin, because the charge distribution on the loop 1 and K 1 may be correlated (Wang and Kawai 2001); loop 1 comes close to the ATP binding site. It is possible that the position of loop 1 changes according to the strain on the myosin head, and this change in turn alters the ATP binding to the myosin head.…”
Section: Tropomyosin or Troponin?mentioning
confidence: 99%